Pentahelix Stakeholder Collaboration In Climate Change Mitigation In Bojonegoro District - Jelita Nur Fitria Anggita; Esa Septian; Rupiarsieh (Jurnal Niara, 2025)
This research aims to describe the roles and contributions of pentahelix stakeholders in the collaboration process on the implementation of climate change mitigation in Bojonegoro Regency. This research method uses a case study approach with a descriptive qualitative research type. Data collection techniques were conducted through interviews, observation, and documentation. The results of this study show that the implementation of climate change mitigation in Bojonegoro Regency is exemplary; the stakeholders involved have played their roles by contributing according to their respective main tasks and functions. The government, as the leading sector, plays a role in policy formulation and facilitates all stakeholders. The community plays a role in community development and becomes a bridge between the community and the government. Businesses contribute in terms of partnerships and funding. Academics run by conducting research and innovation; besides that, the media, in this case, plays a role as a source of information, education and literacy for the public. However, in the implementation of collaboration, there are still problems in the relationship between stakeholders; namely, there is a sectoral ego or silo mentality between stakeholders who tend not to want to share information with other stakeholders. This is one of the challenges and obstacles in the implementation of climate change mitigation in Bojoengoro District.